Regulatory dynamics distinguishing desiccation tolerance strategies within resurrection grasses. (13th December 2022) - St. Aubin, Brian; Wai, Ching Man; Kenchanmane Raju, Sunil K.; Niederhuth, Chad E.; VanBuren, Robert
Abstract: Desiccation tolerance has evolved recurrently in grasses using two unique strategies of either protecting or dismantling the photosynthetic apparatus to minimize photooxidative damage under life without water (anhydrobiosis). Here, we surveyed chromatin architecture and gene expression during desiccation in two closely related grasses with distinguishing desiccation tolerance strategies to identify regulatory dynamics underlying these unique adaptations. In both grasses, we observed a strong association between nearby chromatin accessibility and gene expression in desiccated tissues compared to well‐watered, reflecting an unusual chromatin stability under anhydrobiosis. Integration of chromatin accessibility (ATACseq) and expression data (RNAseq) revealed a core desiccation response across these two grasses. This includes many genes with binding sites for the core seed development transcription factor ABI5, supporting the long‐standing hypothesis that vegetative desiccation tolerance evolved from rewiring seed pathways. Oropetium thomaeum has a unique set of desiccation induced genes and regulatory elements associated with photoprotection, pigment biosynthesis, and response to high light, reflecting its adaptation of protecting the photosynthetic apparatus under desiccation (homoiochlorophyly). By contrast, Eragrostis nindensis has unique accessible and expressed genes related to chlorophyll catabolism, scavenging of amino acids, and hypoxia, highlighting its poikilochlorophyllous adaptations of dismantling the photosynthetic apparatus and degrading chlorophyll under desiccation. Together, our results highlight the complex regulatory and expression dynamics underlying desiccation tolerance in grasses.